DISPUTES AND METHODS OF ITS RESOLUTION (British Journal of Global Ecology and Sustainable Development, 2024)
The article describes the conflicts that occur in personal activity, their types, reasons for their origin, types and procedures for their resolution. In addition, there are ideas about the ways to prevent the pedagogical and psychological characteristics of conflicts, thereby professional deformation.